3D silicon detectors for neutron imaging applications. (1st January 2023) - Povoli, M.; Kok, A.; Koybasi, O.; Getz, M.; O'Neill, G.; Roehrich, D.; Monakhov, E.; Pedersen, H.; Birch, J.; Choolakkal, A.H.; Kanaki, K.; Lai, C.-C.; et al.
Abstract: Neutron detection is of great importance in many fields spanning from scientific research, to nuclear science, and to medical application. The development of silicon-based neutron detectors with enhanced neutron detection efficiency can offer several advantages such as spatial resolution, enhanced dynamic range and background discrimination. In this work, increased detection efficiency is pursued by fabricating high aspect ratio 3D micro-structures filled with neutron converting materials (B4 C) on planar silicon detectors. An in-depth feasibility study was carried out in all aspects of the sensor fabrication technology. Passivation of the etched structures was studied in detail, to ensure good electrical performance. The conformal deposition of B4 C with a newly developed process showed excellent results. Preliminary electrical characterisation of the completed devices is promising, and detectors have been mounted on dedicated boards in view of the upcoming tests with neutrons.